2016
DOI: 10.1080/09613218.2017.1241472
|View full text |Cite
|
Sign up to set email alerts
|

Overheating in Scotland: contributing factors in occupied homes

Abstract: There is growing awareness of the overheating risks in new-build properties in the UK. However, this tends to be considered a problem principally for the southern regions in the UK, only becoming a serious issue in the North of England in the medium term and in the long term for Scotland. This notion tends to be largely predicated upon climate change predictions, differences in latitude and summer air temperatures. This paper describes the results from Building Performance Evaluation (BPE) studies over a two-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 9 publications
(16 reference statements)
1
32
2
Order By: Relevance
“…Living without thermal retrofit: behavioural options and communication challengesOptimising window ventilation at night (cf.Figure 9)shows the enormous influence of residents on overheating, which has also been confirmed by previous studies(Bouchama et al 2007;Ezratty & Ormandy 2015;Lomas & Porritt 2016;Toulemon & Barbieri 2008;Vandentorren et al 2006). This result applies to both retrofitted and non-retrofitted buildings, confirming the ' occupancy overrides design' principle(Morgan, Foster, Poston, & Sharpe 2016). This opens further potential for improving climate justice, particularly for the most disadvantaged.…”
supporting
confidence: 84%
“…Living without thermal retrofit: behavioural options and communication challengesOptimising window ventilation at night (cf.Figure 9)shows the enormous influence of residents on overheating, which has also been confirmed by previous studies(Bouchama et al 2007;Ezratty & Ormandy 2015;Lomas & Porritt 2016;Toulemon & Barbieri 2008;Vandentorren et al 2006). This result applies to both retrofitted and non-retrofitted buildings, confirming the ' occupancy overrides design' principle(Morgan, Foster, Poston, & Sharpe 2016). This opens further potential for improving climate justice, particularly for the most disadvantaged.…”
supporting
confidence: 84%
“…From the evidence available to us, we have identified that perceived overheating during summer occurs all across Europe, including within countries that have milder climates and where this phenomenon was thought to be rare, such as the UK (Morgan et al, 2017). The findings have also revealed driving forces of vulnerability to excessive indoor heat.…”
Section: Discussionmentioning
confidence: 99%
“…Of the European literature that does exist on cooling in buildings and vulnerability, a large proportion of papers take a technical perspective on temperature measurement and adaption, such as a Special Issue on overheating in buildings edited by Lomas and Porritt (2016). This work establishes that overheating is a phenomenon that is already occurring in regions that were thought to be at low risk, such as within Scotland (Morgan et al, 2017), and that it disproportionately occurs within vulnerable households (Vellei et al, 2017). Within Spain, researchers have begun to propose new methods for including energy cooling needs within the definition of energy poverty (Sánchez-Guevara Sánchez et al, 2017) by exploring temperature thresholds specific to the Spanish context.…”
Section: Introductionmentioning
confidence: 99%
“…If proper instructions and guidance are given, problems in installation and commissioning could be prevented, thus averting problems with operation and performance. Recent studies have also found incidents of overheating in Passivhaus [104,108,109], complaints regarding the noise of the MVHR [62,91,104,105], cold draughts [104] and occupants' experiences when interacting with the ventilation unit [70]. These problems may lead to the intermittent or seasonal use of MVHR systems as one of the many occupant responses to such deficiencies.…”
Section: Mvhr Systemsmentioning
confidence: 99%